2018
DOI: 10.1097/sap.0000000000001665
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Tobacco Exposure and Development of Orofacial Clefts in the Child

Abstract: Introduction The purpose of this study was to evaluate the association between maternal tobacco exposure and development of orofacial clefts (OFCs) in the child in a Pakistani population. Methods A case-control study was conducted at the Cleft Hospital and Bashir Hospital in Gujrat, Pakistan, from December 2015 to December 2016. All new cases of OFC at the Cleft Hospital were included. Patients at Bashir Hospital younger than 3 years and without congeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Evidence illustrates that CL/P is a complex, heterogeneous and multifactorial disorder (Buyu et al, 2012;Kalaskar et al, 2013;Bui et al, 2018a) as demonstrated by the variety of biological and/or environmental risk factors found in this systematic review. Lower-middle-income countries present with higher birth rates as well as higher mortality rates compared to highincome countries (The World Bank, 2021a, 2021b) making it difficult to analyze risks from high-income countries in LMICs.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Evidence illustrates that CL/P is a complex, heterogeneous and multifactorial disorder (Buyu et al, 2012;Kalaskar et al, 2013;Bui et al, 2018a) as demonstrated by the variety of biological and/or environmental risk factors found in this systematic review. Lower-middle-income countries present with higher birth rates as well as higher mortality rates compared to highincome countries (The World Bank, 2021a, 2021b) making it difficult to analyze risks from high-income countries in LMICs.…”
Section: Discussionmentioning
confidence: 66%
“…To date, no systematic review has investigated the risks associated with CL/P in LMICs. Low socioeconomic status (SES) was reported to be statistically significantly associated with CL/P in 4 studies (P < .05; Bui et al, 2018aBui et al, , 2018bAli & Hamid, 2019;Gendel et al, 2019). The type of cleft has been linked to different SES levels, as cleft lip (CL) was found to be more prevalent in a low SES population (Gendel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations